Citric Acid Production by Wild and UV – Treated Strains of Aspergillus niger on Two Different Mineral Salt Media - Anyanwu, Valentine Enyinna; Okerentugba, Phillip O. (International Journal of Applied Sciences and Biotechnology, 2013)
Microbial production of citric acid by a novel Aspergillus niger EE-12 and its UV – treated strain (UV-1) were carried out in shake flask cultures using mineral salt media containing sucrose or fructose as the carbon and energy sources. The highest citric acid concentration (36.1g/l) was obtained with the UV – treated strain UV-1 after 144 hours in medium containing sucrose and this was significantly higher (p<0.05) than the concentration produced by its parent strain EE-12. Citric acid production using medium containing sucrose (Sucrose salt medium) was significantly higher (p<0.05) than from medium containing fructose (Fructose salt medium) for both organisms. Product and growth yield coefficients (YCA/S, YCA/F, YCA/X, YX/S, YX/F) and volumetric rates (QF, QS, QCA, QX) were studied and compared for each of the test organisms based on the media (sucrose and fructose salt media) using students t-test analysis. This research indicated that the fungi strains are efficient for citric acid production using sucrose based medium. DOI: http://dx.doi.org/10.3126/ijasbt.v1i3.8358 Int J Appl Sci Biotechnol, Vol. 1(3) 2013 : 145-153